Siglec-15 antibody–GM-CSF chimera suppresses tumor progression via reprogramming tumor-associated macrophages - Jun Li; Hongyan Li; Zemeng Ma; Xiaoyao Hao; Wenwen Dai; Jinyu Liu; Mingjiu Chen; Shuang Qu; Quanli Zhang; Jiajing Luo; Shouyong Gu; Dihan Zhu; et al. (Journal for ImmunoTherapy of Cancer)
Background Sialic acid-binding immunoglobulin-like lectin (Siglec)-15-expressing tumor-associated macrophages (TAMs) drive immunosuppression in the tumor microenvironment (TME), promoting CD8+ T cell exhaustion and limiting immunotherapy efficacy. Both blockade of immune checkpoint molecule Siglec-15 and promotion of granulocyte-macrophage colony-stimulating factor (GM-CSF) have been respectively employed in anticancer immunotherapy.Methods Murine CT26 or MC38 cancer cells were used to establish subcutaneous tumor models in BALB/c or C57BL/6 mice. Tumors were treated with anti-Siglec-15 antibody–GM-CSF chimera (anti-S15×GM CSF) or anti-Siglec-15 antibody via intraperitoneal injection. The TME was analyzed by flow cytometry and ELISA for immune cell infiltration and cytokine levels. Biodistribution and half-life of anti-S15×GM CSF were assessed by intravenous injection in tumor-bearing mice, with GM-CSF levels measured by ELISA. Macrophage reprogramming and antigen presentation were evaluated using bone marrow-derived macrophages and human peripheral blood mononuclear cell-derived macrophages treated with anti-S15×GM CSF, followed by flow cytometry and immunofluorescence assays.Results Here we report that anti-S15×GM CSF displays superior function to suppress the progression of Siglec-15-overexpressing MC38 colon cancer engrafted in mice compared to anti-Siglec-15 antibody or GM-CSF alone. Different from the injected GM-CSF which is distributed broadly in various organs and tissues of mouse, the injected anti-S15×GM CSF is preferentially accumulated in Siglec-15-positive tumor cells and TAMs. Anti-S15×GM CSF not only extends the half-life of GM-CSF in vivo, but also reduces the off-target effect of GM-CSF through TAM-specific delivery. In addition to Siglec-15 blockade, anti-S15×GM CSF effectively reprograms immunosuppressive TAMs to a proinflammatory phenotype, enhancing antigen presentation by macrophages to activate T cells.Conclusions In summary, our results reveal that anti-S15×GM CSF may serve as an effective therapeutic approach for solid tumors.